ОСНОВНЫЕ ЭТАПЫ ИСТОРИИ РЕЧНЫХ ДОЛИН ЦЕНТРА РУССКОЙ РАВНИНЫ В ПОЗДНЕМ ВАЛДАЕ И ГОЛОЦЕНЕ: РЕЗУЛЬТАТЫ ИССЛЕДОВАНИЙ В СРЕДНЕМ ТЕЧЕНИИ Р. СЕЙМ - Панин А.В.; Сидорчук А.Ю.; Баслеров С.В.; Борисова О.К.; Ковалюх Н.Н.; Шеремецкая Е.Д. (My University, 2001)
The main fluvial development stages of the Russian Plain have been revealed. The result is based on the investigations of landforms and deposits of low terraces, flood-plains and river channels of Seim and Svapa rivers. These stages are: 1) 17-19 Ma B.P. - formation of constrative alluvium layers of sand and siltstone more than 10 m thick; 2) 14-17 Ma - formation of the large meandering river channels with discharge 6-7 times more and normal alluvium thick 1.5-2 times more than recent; 3) 10-14 Ma - the reduction of large channels and formation of inherited flood-plains and its deposits; 4) less than 10 Ma - formation of recent meandering river channels and the belt of segment-ridges flood-plain under the conditions of long-period changes of water discharge.
Keywords: Голоцен; Кайнозой::Четвертичная::Голоцен